TRANSFORMATION REFLEXES OF PRE-CHRISTIAN WORLDVIEW IN KIEVAN RUS LITERATURE - Nataliia O. Stratonova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of this article is to review the literature of Kievan Rus' in the light of interaction and mutual influence of Christian and pre-Christian worldviews; to open and show the character of the relations of pre-Christian and Christian religions; to reveal some aspects of these relationships in the literature of Kievan Rus in XI-XIII centuries. Methodology. Among the general scientific approaches in solving the problems that have been used was primarily theological and philosophical. This approach allowed us to explore and objectively analyze the tendency to reflect pre-Christian beliefs in the literature of Kievan Rus. As specially-scientific methods there were used historiosophical (philosophical understanding of historical events and processes), topical (selection and analysis of the basic conceptual directions of transformations), chronological (link historiographical tradition with a concrete historical reality) and the philosophical and hermeneutical (theological-philosophical interpretation of monuments). Scientific novelty. The work is theological and philosophical reflection analysis of pre-Christian ideas in literary monuments of Kievan Rus. For the first time takes into account the specifics of medieval imagination and poetry, studied the religious significance of the texts found their reflection in the pre-Christian beliefs and stated on their role in shaping the world Kievan Rus’ scribes, analyzed the specificity of interaction between Christian and pagan notions. Conclusions. In the process, the author comes to the conclusion that by denying the fact of paganism, separating itself along with other Orthodox nations from the "Latins" and "heretics", Rus claimed its identity through the adoption of Christianity. This process has had its impact on the internal development of the mythodogical consciousness of the people, has accelerated the emergence of the epic in his heroic cycles and Kiev, where it was easy, but dosed and originally instilled Christian ritual principles and values.Byzantine and Bulgarian literature’s circle passed to Russ ready and clear truth, and Rus scribes were the first who learnedit as a model for their life. It is practical, saint idea became the basis of Rus literacy. The apparent ease of assimilation of people outside of the Orthodox Church with the epic structure is not set to culture in general, the problem of conscious, long and organized opposition to the new faith and the old folk pagan wisdom, representatives of which remained "team change people's consciousness," because she folk wisdom in his epic the design principles adopted ritual orthodoxy.